UJI PUPUK KALIUM TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays L. saccharata Sturt) - Arsyad, Muh; Fatmawati, Fatmawati; Fazriyah, Nur (Institute of Computer Science (IOCS), 2026)
Sweet corn (Zea mays L. Saccharata Sturt) is a grain crop that has a high economic value and has the potential to be cultivated because corn is a source of carbohydrates and protein after rice. This research was conducted in Palopo Village, Marisa District, Pohuwato Regency, Gorontalo, in the experimental field of the Agrotechnology Study Program, Faculty of Agriculture and Fisheries Sciences, Pohuwato University. This study aims to determine the effect of potassium fertilizer use on the growth and production of sweet corn. The effect of potassium fertilization on the growth of sweet corn has a significant effect on cob length, cob weight without husk, and the most significant effect is on the parameter of the degree of sweetness. The effect of potassium fertilizer with the best average is in the KCl2 treatment and for the treatment with the lowest average is in the KCl0 treatment. While the effect of potassium fertilizer with the highest KCl3 treatment does not always increase yields significantly.